THE PARADIGM OF ISLAMIC VALUE-BASED SOCIAL COMMUNITY COUNSELING IN ADDRESSING PSYCHOSOCIAL PROBLEMS - Nunik Nurhozanah; Aep Kusnawan; Sugandi Miharja (AL-TAZKIAH, 2026)
Contemporary psychosocial problems have become increasingly complex due to social change, economic pressure, disruptions in social relationships, and the weakening of spiritual sources of meaning in collective life. Global data indicate that nearly one in seven people lived with a mental disorder in 2021, while national data show that the prevalence of depression among people aged 15 years and older reached 1.4%, with the 15-24 age group having the highest prevalence. This article aims to formulate a paradigm for Islamic value-based social community counseling to address psychosocial problems. This study employs qualitative library research, using thematic analysis and a conceptual synthesis of the literature on community counseling, Islamic guidance and counseling, community psychology, mental health, and recent empirical data. The findings indicate that the Islamic community counseling paradigm is constructed through the integration of tawhid, ukhuwah, social justice, maslahah, amanah, shura, and ta'awun with the principles of participation, empowerment, advocacy, prevention, and community evaluation. The contribution of this study lies in the formulation of a conceptual-operational model that positions counselors as facilitators, educators, mediators, advocates, social network mobilizers, and value guardians. The article recommends developing community counseling programs within mosques, religious social institutions, families, schools, and through cross-sector collaboration, and testing them using psychological, social, spiritual, and structural indicators.